Miltonic Diplomacy in Queen Elizabeth II’s Golden Wedding Speech. - Philippa Earle (Royal Studies Journal)
That Prince Philip was Queen Elizabeth II’s “strength and stay” came to memorialize their relationship. This article shows that the Queen’s now familiar words in fact are those of the great British poet, John Milton (1608-1674), from his epic retelling of the biblical Fall, Paradise Lost (1667/1674). Appreciating how and why Elizabeth integrates the quotation from Paradise Lost in the Golden Wedding anniversary speech (20 November, 1997) sheds light on the value of literature and Milton’s poem, specifically, to the Queen’s diplomacy after the death of Princess Diana. The Queen’s immediate response to the tragedy, she came to understand, made the monarchy’s future precarious. In consequence of the public reaction and a series of royal humiliations prior, Queen Elizabeth alludes to, and further, adopts in the Golden Wedding speech the reconciliatory humility of Milton’s Eve; the character who, through “fault / Acknowledged” appeals to her “strength and stay” (PL 10.938-939, 921). This article ultimately argues that, by establishing a Miltonic diplomacy in the Golden Wedding speech, the Queen cleverly encompasses and solidifies both her private, political, and public relationships in the nuptial symbolism of the occasion.